The Early Modern Teacher: Marie Dentière: An Outspoken Reformer Enters the French Literary Canon - McKinley, Mary B. (The sixteenth century journal, 2006)
For ten years, the University of Chicago Press has been publishing the series The Other Voice in Early Modern Europe, edited by Margaret L. King and Albert Rabil Jr. This series publishes translations and editions of works written during the period 1300-1700 that in some way challenge the dominant negative view of women. Most of these texts are by women, and with forty-four works in the series by December 2006, the books have become important teaching tools for courses about women or more general courses. Later this year, the press will publish a book of essays, "Teaching Other Voices: Women and Religion in Early Modern Europe", also edited by King and Rabil, designed to provide practical guidance in using the texts in the series that concern religion. This essay is one that will appear in "Teaching Other Voices", and discusses strategies for teaching Marie Dentière, an author of great interest to many readers of this journal.